Transfemoral transcatheter aortic valve implantation in a patient with multiple endovascular aortic stents – a case report. Issue 1 (December 2016) - Weber, Carolyn; Deppe, Antje-Christin; Eghbalzadeh, Kaveh; Scherner, Maximilian; Gray, Daphne; Majd, Payman; Gawenda, Michael; Rosenkranz, Stephan; Rudolph, Tanja; Madershahian, Navid; Wahlers, Thorsten
Abstract Background In patients undergoing transfemoral transcatheter aortic valve implantation, previous endovascular interventions bear a risk for the valve frame to get stucked to the aortic stents. Case Presentation We report on a 75-year-old frail patient with severe aortic stenosis and a rapid increase of an infra-renal aneurysm. He had a history of multiple endovascular interventions on the aorta. Due to his frail preoperative status we decided to perform a transfemoral transcatheter aortic valve implantation in combination with a simultaneous surgical abdominal aneurysm repair. To allow an atraumatic passage of the Edwards SAPIEN 3 valve across the endovascular stents we used a special technique. Conclusions The transfemoral approach in patients with previous endovascular stenting can be performed successfully by a partial inflation of the distal balloon.